2020
DOI: 10.1002/btpr.3085
|View full text |Cite
|
Sign up to set email alerts
|

Tuning monoclonal antibody galactosylation using Raman spectroscopy‐controlled lactic acid feeding

Abstract: A key aspect of large-scale production of biotherapeutics is a well-designed and consistently-executed upstream cell culture process. Process analytical technology tools provide enhanced monitoring and control capabilities to support consistent process execution, and also have potential to aid in maintenance of product quality at desired levels. One such tool, Raman spectroscopy, has matured as a useful technique to achieve real-time monitoring and control of key cell culture process attributes. We developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…This study compared the metabolic profiles of two experimental treatments of mAb‐expressing GS‐knockout CHO‐K1 cells grown in bioreactors: cells grown with a controlled lactic acid feed designed to maintain lactate at 2 g/L (Lactic acid feed), and cells grown without a lactic acid feed (Control). Feeds were controlled using a feedback control loop informed by Raman spectroscopy (for more detail on this work, please refer to Eyster et al 11 ). For both treatments, glucose was maintained at 4 g/L using a controlled glucose feed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This study compared the metabolic profiles of two experimental treatments of mAb‐expressing GS‐knockout CHO‐K1 cells grown in bioreactors: cells grown with a controlled lactic acid feed designed to maintain lactate at 2 g/L (Lactic acid feed), and cells grown without a lactic acid feed (Control). Feeds were controlled using a feedback control loop informed by Raman spectroscopy (for more detail on this work, please refer to Eyster et al 11 ). For both treatments, glucose was maintained at 4 g/L using a controlled glucose feed.…”
Section: Resultsmentioning
confidence: 99%
“…Details of the model cell line and bioreactor operation used in this study can be found in Eyster et al 11 Briefly, a glutamine synthetase (GS)‐knockout CHO‐K1 cell line was thawed into a proprietary, chemically‐defined seed medium and passaged in shake flasks. At the N‐1 stage, three 3 L Applikon bioreactors with a custom‐built control system were inoculated to a target viable cell density of 0.4 × 10 5 cells/mL at a working volume of 2 L. After 4 days of culture, cells from the two reactors with the highest viable cell count (VCC) were pooled to inoculate eight 3 L production bioreactors to an initial working volume of 1.9 L and target viable cell density of 1.0 × 10 5 cells/mL (one reactor subsequently failed due to a faulty DO probe).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations